COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN WISATA RELIGI MAKAM GUS DUR DI KABUPATEN JOMBANG - Azizah Ramadhani Mega Nahda W; Lukman Arif (Journal Publicuho, 2025)
This study aims to analyse the process of collaborative governance in the development of religious tourism at the Tomb of Gus Dur in Jombang Regency based on the framework by Ansell and Gash (2008). The research uses a descriptive method with a qualitative approach. The findings indicate that the cooperation between the Jombang Regency Office of Youth, Sports, and Tourism (Disporapar) and the Tebuireng Islamic Boarding School was initiated through coordination following a surge of visitors after Gus Dur’s passing, which was not matched by adequate infrastructure. Additionally, the imbalance of authority among human resources also formed the basis for this collaboration. In terms of institutional design, the collaboration is supported by a written agreement titled the joint agreement, signed by both parties. In the dimension of facilitative leadership, Disporapar plays the role of a leader supporting the collaborative process. In the collaborative process itself, face-to-face dialogue was conducted, commitment was demonstrated through the signing of the agreement, mutual understanding was built through discussion forums, and early success of the collaboration was shown by winning the title of Cultural Tourism Attraction at the 2017 East Java Tourism Awards